2020
DOI: 10.1029/2019tc005750
|View full text |Cite
|
Sign up to set email alerts
|

Neogene Basin Inversion and Recent Slip Rate Distribution of the Northern Termination of the Alhama de Murcia Fault (Eastern Betic Shear Zone, SE Spain)

Abstract: The Alhama de Murcia Fault is one of the main active structures of the Eastern Betic Shear Zone (SE Spain), characterized by the presence, along its trace, of Neogene basins developed under early to late Miocene extensional tectonics. A dominant NNW‐SSE shortening direction is active from late Miocene driven by the present‐day plate convergence. We present the structural analysis of the northeastern section of this fault, where reliable estimations of slip rates were unknown due to the lack of geomorphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
(152 reference statements)
0
8
0
1
Order By: Relevance
“…A neotectonic shortening phase started at the end of the Neogene as a result of Eurasia and Africa convergence (Sanz de Galdeano, 1990; Herrero‐Barbero et al., 2020, and references therein). Present‐day convergence rate is about 4–6 mm/yr in a NW‐SE direction based on geodetic and seismological data (see e.g., Koulali et al., 2011; Nocquet, 2012; Serpelloni et al., 2007) and the EBSZ seems to be accommodating up to 31% of the total shortening (Masana et al., 2004).…”
Section: Seismogenic Sources In the Eastern Betic Shear Zonementioning
confidence: 99%
“…A neotectonic shortening phase started at the end of the Neogene as a result of Eurasia and Africa convergence (Sanz de Galdeano, 1990; Herrero‐Barbero et al., 2020, and references therein). Present‐day convergence rate is about 4–6 mm/yr in a NW‐SE direction based on geodetic and seismological data (see e.g., Koulali et al., 2011; Nocquet, 2012; Serpelloni et al., 2007) and the EBSZ seems to be accommodating up to 31% of the total shortening (Masana et al., 2004).…”
Section: Seismogenic Sources In the Eastern Betic Shear Zonementioning
confidence: 99%
“…For instance, Herrero‐Barbero et al. (2020) have interpreted refraction as the cause of dip decrease at the surface in the NE tip of the AMF. The latter model could also be the explanation for a frontal thrust in the transect (F‐AMF) (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a structural control of preexisting Miocene extensional faults in the development of the active transpressive structure of the AMF, for instance at the NE end of the fault (e.g., Herrero-Barbero et al, 2020). Up until the Late Miocene, these faults bounded major sedimentary basins located NW of the modern AMF trace (i.e., Lorca and Fortuna basins; Figure 1c), which then inverted into oblique-reverse faults forming the related thrust-fold ranges of the Las Estancias, La Tercia and Espuña (Martínez-Díaz, 1998;Meijninger & Vissers, 2006;Montenat et al, 1987).…”
Section: Structural and Tectonic Characterization Of The Alhama De Mu...mentioning
confidence: 99%
“…The AMF here has a diffuse geomorphic expression, which can be ascribed to the transfer of the deformation to the nearby Carrascoy fault. Herrero- Barbero et al (2020) estimate a net-slip rate of about 0.32 mm/year in this section for the last 4.8-7.6 Ma, based on GPS convergence vectors and cross-section restorations.…”
Section: Geological Settingmentioning
confidence: 98%